Gaya Komunikasi Dakwah Era Digital: Kajian Literatur - Yulia Rahmawati; Farida Hariyati; Ahmad Zakki Abdullah; Mia Nurmiarani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research provides a deep understanding of the transformation of preaching or dawah communication styles in the digital era. Against the backdrop of technological advancements, preaching is no longer confined to conventional methods but has evolved into multi-directional communication that is more interactive and responsive. Preachers now adopt various strategies to enhance the effectiveness of preaching in the digital world. The research results highlight the shift in preaching communication styles from traditional lectures to utilizing social media, video platforms, and instant messaging applications. Prominent preachers in Indonesia, such as Abdul Somad, Adi Hidayat, and Khalid Basalamah, serve as successful examples in reaching audiences through digital channels. Various strategies for enhancing preaching in the digital era are identified, including mastering various digital platforms, developing storytelling skills, understanding online audience trends and habits, collaborating with digital content creators, implementing interactive technology, optimizing search and online visibility, and maintaining branding and messaging consistency. In conclusion, the utilization of digital technology can create preaching content that is more dynamic, relevant, and easily accessible to audiences increasingly connected through technology. Thus, this research provides practical guidance for preachers and researchers to enhance preaching communication in the digital era, making preaching more effective and relevant in the face of the dynamic developments in communication technology.